2019
DOI: 10.1111/den.13446
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of scissor‐type knives for endoscopic mucosal dissection of superficial gastrointestinal neoplasms

Abstract: Endoscopic submucosal dissection (ESD) for superficial gastrointestinal neoplasms has become widespread. However, certain aspects of the procedure remain difficult to manage, such as intraoperative bleeding and perforation. There are two kinds of scissor‐type knife: the Clutch Cutter (Fujifilm Co., Tokyo, Japan) and the SB knife (Sumitomo Bakelite Co., Tokyo, Japan). These knives have different features from other types of ESD knives and enable the performance of all ESD procedures, including mucosal incision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…In addition, the considerably low rate of adverse events in the introductory period suggests that the procedure is easy and safe. These results are similar to those reported previously with scissor-type knives and indicated that CR-ESD using SB Knife Jr resulted in good short-term outcomes [2][3][4][5][6][10][11][12][13]. Although positive outcomes with CR-ESD have been reported in high-volume centers in Asia (notably Japan) [14][15][16][17][18][19], the adoption of CR-ESD has not been widespread in general hospitals because of the technical challenges posed by the complex anatomic features of the large intestine.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the considerably low rate of adverse events in the introductory period suggests that the procedure is easy and safe. These results are similar to those reported previously with scissor-type knives and indicated that CR-ESD using SB Knife Jr resulted in good short-term outcomes [2][3][4][5][6][10][11][12][13]. Although positive outcomes with CR-ESD have been reported in high-volume centers in Asia (notably Japan) [14][15][16][17][18][19], the adoption of CR-ESD has not been widespread in general hospitals because of the technical challenges posed by the complex anatomic features of the large intestine.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, although CR-ESD using the scissor-type knife is gradually increasing, penetration rates remain low. Our previous study included 247 cases [4], and this sample size was the largest among all studies previously conducted on CR-ESD using scissor-type knives [13]. Furthermore, few previous reports for CR-ESD using SB knife Jr exist in Western countries [27].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Clutch Cutter, which is a scissors-type electrosurgical knife for ESD, is safe and technically efficient for gastric, esophageal, and colorectal ESD. [12][13][14][15][16][17] ESD using Clutch Cutter was reported to be safe for a few patients of duodenal tumors. 18 To prevent delayed complications, we previously reported the safety and feasibility of laparoscopic closure for the prevention of delayed adverse events after ESD.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a precut method using the Clutch Cutter (CC; Fujifilm, Tokyo, Japan). The CC is scissor‐type knife for endoscopic submucosal dissection (ESD) and allows a stable endoscope position during the procedure 5 . Its ability to grasp and release tissue solves many difficulties that face NKF.…”
Section: Brief Explanationmentioning
confidence: 99%